2011
DOI: 10.1007/s12272-011-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

The combination of mixed lactic acid bacteria and dietary fiber lowers serum cholesterol levels and fecal harmful enzyme activities in rats

Abstract: Probiotics such as lactic acid bacteria (LAB) and prebiotics such as fiber are generally considered beneficial for health. These affect the microflora composition and fermentation metabolites and consequently contribute to local and systemic effects in humans. The beneficial effects of probiotics can be improved when combined with prebiotics. Here we investigated the effects of a mixed LAB supplement combined with dietary fiber on the population of LAB in the gut, as well as on serum cholesterol levels, fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…High fiber contents in chia seeds lead to increase the population of LAB and the fecal water content and reduce microbial harmful enzyme (β-glucosidase, β-glucuronidase and tryptophanase) activities. Lee et al,(2011). From the same table it could be also observed that spore form count recorded highest number in yoghurt mousse with 1% chia seeds, followed by the control treatment, while yoghurt mousse with 2% and 3% recorded the lowest spore counts.…”
Section: -Water Holding Capacity (Whc)mentioning
confidence: 57%
“…High fiber contents in chia seeds lead to increase the population of LAB and the fecal water content and reduce microbial harmful enzyme (β-glucosidase, β-glucuronidase and tryptophanase) activities. Lee et al,(2011). From the same table it could be also observed that spore form count recorded highest number in yoghurt mousse with 1% chia seeds, followed by the control treatment, while yoghurt mousse with 2% and 3% recorded the lowest spore counts.…”
Section: -Water Holding Capacity (Whc)mentioning
confidence: 57%
“…Moreover, numerous studies have suggested that some genera of bacteria in gut have the ability to produce harmful enzymes (eg, urease, β-glucuronidase and azoreductase), and potentially toxic compounds (e.g., ammonia) in the intestinal tract [42][43][44]. In the present study, the SCFA fermentation products of FCS-pg result in a lower pH environment (Table 2), which plays a role in inhibiting the growth of pathogenic bacteria and influencing harmful enzyme activities in the human intestine, reducing the intestinal absorption of potentially toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophanase activity was assayed using tryptophan as substrate, and urease activity was determined using urea as substrate. The reactions were measured by spectrophotometry at 405, 550 or 610 nm, respectively (Metrolab 2100, Argentina) [16,25,26].…”
Section: Fecal and Cecum Determinationsmentioning
confidence: 99%
“…NDFO modifies the colonic microbiota increasing the proliferation and activity of beneficial bacteria against pathogenic species [16][17][18][19]. This shift in the composition of the enteric microbiota dramatically changes the bacterial metabolic products released into the gut.…”
Section: Introductionmentioning
confidence: 99%